Mechanical and degradation properties of small-diameter vascular grafts in an in vitro biomimetic environment. (March 2019) - Li, Xiangshun; Zhao, Huijing
Small-diameter vascular grafts may fail after implantation due to various reasons from mechanical and biological aspects. In order to evaluate the mechanical durability of small-diameter vascular grafts after implantation, an artificial vascular biomimetic environment that can simulate body temperature, the liquid environment outside the vessel, and continuous blood flow and pulsatile pressure was constructed. This device can be used as a "pre-test" prior to animal experiments to explore the changes of mechanical and degradation properties in the long-term in vivo environment. At the same time, braided tube-reinforced silk fibroin/poly (l -lactic acid-co-ε-caprolactone) small-diameter vascular grafts were fabricated and tested under the biomimetic environment. Mechanical changes, including tensile properties, suture retention strength, compliance, and degradation behavior of the braided tube-reinforced poly (l -lactic acid-co-ε-caprolactone)/silk fibroin small-diameter vascular grafts were explored over various periods of time in the biomimetic environment. The results shown that under a period of testing in the in vitro biomimetic environment, the comprehensive mechanical properties (including tensile properties, suture retention strength, estimated-bursting pressure, and compliance) of small-diameter vascular grafts exhibited varying degrees of changes but that there was no obvious degradation behavior in the short term.